An experience of using multimodal analgesia in the perioperative period at the medical center "GarvisTM" - Bereznytskyi, Vitalii; Zalyhina, Yevheniia; Nataliia, Skubytska (Pain medicine, 2020)
There is no “gold standard” for the treatment of postoperative pain. According to statistics, from 30 to 75% of patients in the surgical departments continue to suffer from severe pain. Objective. To assess the practical relevance and quality of postoperative pain management using advanced standard operating procedure techniques. Material and methods. Evaluation of performance, safety and pharmacoeconomic feasibility was carried out in accordance with the standard operating procedure (SOP.01-03). Results and discussion. The “GarvisTM Clinic” has introduced a multimodal approach to pain therapy, which is based on the use of paracetamol (infulgan). This drug is characterized by the best price-quality ratio.